Taxonomy of two endemic Indian skinks, Eutropis bibronii (Gray, 1838)and E. nagarjunensis (Sharma, 1969) (Reptilia: Scincidae), including redescriptions of their types - Amarasinghe, A.a. Thasun.; Campbell, Patrick D.; Chandramouli, S.r.; Deuti, Kaushik; Raha, Sujoy; Karunarathna, D.m.s. Suranjan; Ineich, Ivan (Zootaxa, 2016)
Tiliqua bibronii was described by J.E. Gray in December, 1838 based on two syntypes (MNHN-RA 2940, 7076), but the details for locality was missing. These syntypes are currently housed at the Muséum national d’Histoire naturelle, Paris, France (MNHN-RA). The same species (based on the same type specimens) was described by A.M.C. Duméril & G. Bibron in November, 1839 nearly one year after Gray’s publication. As such, Gray’s publication must therefore be given priority. Another species, Euprepis trilineatus, from Madras, Tamil Nadu, India, was described by Gray in 1846, and it is morphologically similar to E. bibronii. Later, Boulenger (1885) synonymised it with E. bibronii. Eutropis bibronii has subsequently been recorded from other parts of India and Sri Lanka by various authors. Many years later, a closely related species, Mabuya nagarjuni (sic) Sharma, 1969, was described from Andhra Pradesh, India, based on two specimens (a holotype and a paratype) housed at the Zoological Survey of India, Kolkata (ZSI). Here we make a correction for the species epithet as “nagarjunensis” which should be a toponym, not a patronym. Among the skink collections at the Natural History Museum, London (BMNH), ZSI, and MNHN-RA we found E. bibronii specimens collected from various locations in India, but we were unable to find any specimens from Sri Lanka. Based on morphological evidence, E. bibronii represents a single, fairly widespread, species which has to be considered endemic to India. Although, recent phylogenetic studies reveal a distinct genetic divergence between E. bibronii and E. nagarjunensis, both species are morphologically very similar to each other. Here, we examine the morphology of E. nagarjunensis based on the ZSI specimens. A comprehensive comparison between the syntypes of E. bibronii and Euprepis trilineatus confirms that the latter nomen is a junior synonym of the former. The original description of E. bibronii is extremely concise and lacks most of the important diagnostic characters, so here we provide a comprehensive redescription of the species based on the examination of its syntypes.